Betalains: Biomolecular Aspects - Akbar Hussain, Erum (Springer International Publishing, 2018)
This unique text provides comprehensive coverage of betalains, outlining the specific makeup and uses of this plant. The chapters provide deep insight into the biosynthesis, structures, pharmacokinitics, stability, extraction, health benefits and occurrence in nature of betalains. As the first major reference work to focus specifically on betalains, this book serves as an important reference for any researcher looking for insights into the use of betalains as functional foods, food coloring agents, and nutraceuticals. Betalains: Biomolecular Aspects outlines the chemical structure of betalains, including their occurrence in nature. The utilization of of these plants as natural color in food and beverages is covered in depth, as are the intake and secretion of betalains in the human body. The various factors affecting the stability of betalains are described, including their stability when used in food products. Current health related uses for these plants are outlined, including antioxidant and anti-inflammatory uses. The isolation and purification of these plants, plus analysis techniques, are outlined. In providing extensive coverage of betalains and their uses, this text presents a singular work which is of major value for a wide range of researchers. .